ChemInform Abstract: In(OTf)3 Catalyzed an Expeditious Synthesis of β‐Carboline—imidazo[1, 2‐a]pyridine and Imidazo[1, 2‐a]pyrazine Conjugates. Issue 38 (September 2016) - Devi, Nisha; Singh, Dharmender; Honey, Honey; Mor, Satbir; Chaudhary, Sandeep; Rawal, Ravindra K.; Kumar, Vipin; Chowdhury, Asim K.; Singh, Virender
Abstract: by efficient In(OTf)3 assisted Groebke‐Blackburn‐Bienayme multicomponent strategy